# ISI2017-DCG-5

56 views

The sum of the squares of the roots of $x^2-(a-2)x-a-1=0$ becomes minimum when $a$ is

1. $0$
2. $1$
3. $2$
4. $5$

recategorized

1 vote

Let $\alpha, \beta$ are the roots of the given equation.

Then $\alpha + \beta = a-2$, $\alpha. \beta= 1-a$

$(\alpha + \beta)^2= \alpha^2 + \beta^2 + 2 \alpha \beta$

$(a-2)^2= \alpha^2 + \beta^2 + 2 - 2a$

$\alpha^2 + \beta^2= a^2 -2a +2= x$(let)

We have to minimize $x$, differentiating $x$ wrt to $a$

$\frac{dx}{da} = 2a-2 = 0, a=1$

$\frac{d^2 x} {d a^2} = 2 > 0$(minima)

So for $a=1$, $x$ will be minimum.

Hence option B) is correct

edited
0
Here in the second last line  for getting local minima $\dfrac{\mathrm{d}^{2}x }{\mathrm{d} a^{2}}=2>0$

## Related questions

1 vote
1
94 views
Consider the equation $P(x) =x^3+px^2+qx+r=0$ where $p,q$ and $r$ are all real and positive. State which of the following statements is always correct. All roots of $P(x) = 0$ are real The equation $P(x)=0$ has at least one real root The equation $P(x)=0$ has no negative real root The equation $P(x)=0$ must have one positive and one negative real root
Let $x^2-2(4k-1)x+15k^2-2k-7>0$ for any real value of $x$. Then the integer value of $k$ is $2$ $4$ $3$ $1$
If $\alpha$ and $\beta$ be the roots of the equation $x^2+3x+4=0$, then the equation with roots $(\alpha + \beta)^2$ and $(\alpha – \beta)^2$ is $x^2+2x+63=0$ $x^2-63x+2=0$ $x^2-2x-63=0$ None of the above
If $r$ be the ratio of the roots of the equation $ax^{2}+bx+c=0,$ then $\frac{r}{b}=\frac{r+1}{ac}$ $\frac{r+1}{b}=\frac{r}{ac}$ $\frac{(r+1)^{2}}{r}=\frac{b^{2}}{ac}$ $\left(\frac{r}{b}\right)^{2}=\frac{r+1}{ac}$